2012
DOI: 10.1097/mao.0b013e3182635417
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Inflammatory Biomarkers With the Onset and Prognosis of Idiopathic Sudden Sensorineural Hearing Loss

Abstract: Neutrophil counts above the reference range of a facility will be a useful indicator of poor prognosis of ISHL. Synchronism of different types of NF-κB activation pathways could be required to cause severe ISHL. An NKCA decrease, an acute neutrophil count increase, and an IL-6 increase can induce NF-κB activation in the cochlea and cause severe ISHL. Further epidemiologic surveys should be conducted to evaluate whether stressful life events increase the risk of severe ISHL onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
136
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 65 publications
(36 reference statements)
6
136
0
3
Order By: Relevance
“…In particular, Seo et al (2014) and Kum et al (2015) showed lower values of lymphocyte count in patients with less than 15 dB HL of hearing gain with respect to the initial hearing loss. Masuda et al (2012), _ Ikinciogullar{ et al (2014) and Quaranta et al (2015) instead did not observe any correlation between lymphocyte count and recovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Seo et al (2014) and Kum et al (2015) showed lower values of lymphocyte count in patients with less than 15 dB HL of hearing gain with respect to the initial hearing loss. Masuda et al (2012), _ Ikinciogullar{ et al (2014) and Quaranta et al (2015) instead did not observe any correlation between lymphocyte count and recovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that neutrophil counts above the reference range could be a useful indicatior of poor prognosis of ISSNHL; however, hs-CRP did not seem to be a useful biomarker [18] . Similarly, hs-CRP levels were not significantly higher in ISSNHL patients than in controls in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Masuda et al [18] investigated whether inflammatory markers, including leukocyte counts, natural killer cell activity (NKCA), interleukin 6 (IL-6) level, tumor necrosis factor level, and high-sensitivity CRP level, are involved in the pathophysiology of idiopathic sensorineural hearing loss. They suggested that neutrophil counts above the reference range could be a useful indicatior of poor prognosis of ISSNHL; however, hs-CRP did not seem to be a useful biomarker [18] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact etiopathogenesis of the ISSNHL is still unclear. Microcirculatory failure, infectious, immunologic, and inflammatory reasons have been hypothesized [3,4]. According to the viral theory, ISSNHL is due to a herpes simplex virus infection; however, no specific serological profiles or response to antiviral treatment has been reported [2].…”
Section: Discussionmentioning
confidence: 99%
“…A number of etiologies of ISSNHL have been proposed, including viral infection, vascular disturbance, and immune-mediated mechanisms. However, there is no conclusive evidence for any particular hypothesis [2][3][4]. The cause of ISSNHL has been focused on chronic inflammation recently [5].…”
Section: Introductionmentioning
confidence: 99%